Meta-analysis of Genome-Wide Association Studies for Extraversion: Findings from the Genetics of Personality Consortium - van den Berg, Stéphanie M.; de Moor, Marleen H. M.; Verweij, Karin J. H.; Krueger, Robert F.; Luciano, Michelle; Arias Vasquez, Alejandro; Derringer, Jaime; Esko, Tõnu; Amin, Najaf; Gordon, Scott D.; Hansell, Narelle K.; Hart, Amy B.; et al. (Behavior genetics, 2016)
Extraversion is a relatively stable and heritable personality trait associated with numerous psychosocial, lifestyle and health outcomes. Despite its substantial heritability, no genetic variants have been detected in previous genome-wide association (GWA) studies, which may be due to relatively small sample sizes of those studies. Here, we report on a large meta-analysis of GWA studies for extraversion in 63,030 subjects in 29 cohorts. Extraversion item data from multiple personality inventories were harmonized across inventories and cohorts. No genome-wide significant associations were found at the single nucleotide polymorphism (SNP) level but there was one significant hit at the gene level for a long non-coding RNA site (LOC101928162). Genome-wide complex trait analysis in two large cohorts showed that the additive variance explained by common SNPs was not significantly different from zero, but polygenic risk scores, weighted using linkage information, significantly predicted extraversion scores in an independent cohort. These results show that extraversion is a highly polygenic personality trait, with an architecture possibly different from other complex human traits, including other personality traits. Future studies are required to further determine which genetic variants, by what modes of gene action, constitute the heritable nature of extraversion.